2019
DOI: 10.1186/s12879-019-3928-0
|View full text |Cite
|
Sign up to set email alerts
|

Human rabies post exposure prophylaxis at the Pasteur Institute of Dakar, Senegal: trends and risk factors

Abstract: Background Rabies remains a major public health problem in developing countries. Most fatal rabies cases, especially in children, result from dog bites and occur in low-income countries, such as those in Sub-Saharan Africa. Rabies can be controlled through mass dog vaccination and human deaths prevented through timely and appropriate post-exposure prophylaxis (PEP). As access to appropriate PEP remains a serious challenge for bite-victims, the aim of this study was to understand the use of PEP, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 34 publications
5
37
2
Order By: Relevance
“…Moreover, in our study, those with secondary education or more were more likely to access information on dogs and dog bites than those with less education level. Our findings and probable explanation are coherent with research that has suggested that people with higher education tend to have more knowledge about rabies than illiterate ones [46,47].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, in our study, those with secondary education or more were more likely to access information on dogs and dog bites than those with less education level. Our findings and probable explanation are coherent with research that has suggested that people with higher education tend to have more knowledge about rabies than illiterate ones [46,47].…”
Section: Plos Onesupporting
confidence: 91%
“…applied on the wound by the 193 victims who conducted some pre-clinical care were antiseptic (46), herbs (25) black stone (10) unknown creams or other materials such as beans, dog urine, dust, tobacco, coins, brake fluid, acid, powder made out of dog hair and salt. Notably, only 8 out of 29 study participants who had at least one previous dog bite episode complied with preclinical guidelines.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, in our study, those with secondary education or more were more likely to access information on dogs and dog bites than those with less education level. Our findings and probable explanation are coherent with research that has suggested that people with higher education tend to have more knowledge about rabies than illiterate ones [44,45].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is not unique to Benin. Other studies conducted in India and Senegal had respondents report poor compliance with PEP treatment due to the cost [ 19 , 20 ]. Due to this financial burden, the majority of our study´s respondents noted that using traditional recipes which lack empirical evidence of successful rabies treatment increases the risk of a community´s rabies incident.…”
Section: Discussionmentioning
confidence: 99%